Fundamentals of electromagnetics - Miah, M. A. Wazed (San Rafael, Calif. (1537 Fourth Street, San Rafael, CA 94901 USA) : Morgan & Claypool Publishers, 2007)
This book is the first of two volumes which have been created to provide an understanding of the basic principles and applications of electromagnetic fields for electrical engineering students. Fundamentals of Electromagnetics Vol 1: Internal Behavior of Lumped Elements focuses upon the DC and low-frequency behavior of electromagnetic fields within lumped elements. The properties of electromagnetic fields provide the basis for predicting the terminal characteristics of resistors, capacitors, and inductors. The properties of magnetic circuits are included as well. For slightly higher frequencies for which the lumped elements are a significant fraction of a wavelength in size the second volume of this set, Fundamentals of Electromagnetics Vol 2: Quasistatics and Waves, examines how the low-frequency models of lumped elements are modified to include parasitic elements. Upon completion of understanding the two volumes of this book, students will have gained the necessary knowledge to progress to advanced studies of electromagnetics.
Preface -- 1. Resistors -- 1.1. Resistors : a first glance -- 1.2. Modeling and approximations -- 1.3. Voltage drop, voltage, and fields -- 1.4. Electric field intensity -- 1.5. Generalized coordinates -- 1.6. Voltage gradient -- 1.7. [Delta]V and equipotentials -- 1.8. Voltage drop and line integrals -- 1.9. KVL and conservative fields -- 1.10. Evaluation of line integrals -- 1.11. Numeric approximation -- 1.12. Analytic evaluation -- 1.13. Current and current density -- 1.14. Currents and surface integrals -- 1.15. Charge conservation and KCL -- 1.16. Evaluation of surface integrals -- 1.17. Numeric evaluation -- 1.18. Analytic evaluation -- 1.19 Divergence -- 1.20. Flux tubes -- 1.21. Divergence theorem -- 1.22. Charge conservation revisited -- 1.23. Ohm's law -- 1.24. Conductivity -- 1.25. Boundary conditions -- 1.26. Incremental resistors -- 1.27. Curvilinear squares -- 1.28. Laplace's equation -- 1.29. Analytic solution methods -- 1.30. Numeric methods -- 1.31. Linear equations -- 1.32. Iterative techniques -- 1.33. Resistance calculations -- 1.34. Circuit analogs -- 1.35. Power dissipation -- 2. Capacitors -- 2.1. Capacitors : a first glance -- 2.2. Charges On electrodes -- 2.3. Gauss' law -- 2.4. Divergence of D -- 2.5. Dielectric permittivity -- 2.6. Dielectric boundary conditions -- 2.7. Flux tubes, equipotentials, and capacitance -- 2.8. Capacitance : a closer look -- 2.9. Laplace's equation revisited -- 2.10. Electric energy storage -- 2.11. Capacitance calculations -- 2.12. Forces and virtual work -- 2.13. Flux density via Gauss' law -- 2.14. Arbitrary charge distributions -- 3. Inductors -- 3.1. Inductors : a first glance -- 3.2. Magnetic flux density -- 3.3. Ampere's law and magnetic field intensity -- 3.4. Magnetic fields in cores -- 3.5. Magnetic permeability -- 3.6. Magnetic boundary conditions -- 3.7. Faraday's law -- 3.8. Self inductance -- 3.9. Magnetomotive force -- 3.10. Magnetic energy storage -- 3.11. Inductance calculations -- 3.12. Mutual inductance -- 3.13. Ampere's law revisited and the curl operator -- 3.14. Arbitrary current distributions and the Biot-Savart law -- 3.15. Field intensity via Ampere's law -- 4. Magnetic devices -- 4.1. Magnetic circuits : the basics -- 4.2. Magnetic circuits : more details -- 4.3. Magnetic circuits with air gaps -- 4.4. Nonlinear magnetic circuits -- 4.5. Transformers -- 4.6. Magnetic forces -- 4.7. Solenoids -- 4.8. Relays -- 4.9. Faraday's law revisited -- Author biography.
Part of: Synthesis digital library of engineering and computer science.
Title from PDF t.p. (viewed Oct. 19, 2008).
Series from website.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat Reader.
Keywords: Capacitors; Electric inductors; Electric resistors; Electromagnetic fields; Electromagnetism; Lumped elements (Electronics); Magnetic circuits